Implementation of Problem-Based Learning Model Using Youtube Media to Improve Numeracy Literacy of 8th Grade Students - Lestari, Ririn Umi; Widiansyah, Arindra Trisna (Science Education and Application Journal, 2025)
Application of Problem-Based Learning Model Based on Youtube Media to Improve Students’ Numeracy Literacy. In eighth grade, kids' limited numeracy literacy abilities make it difficult for them to understand science. One innovative solution is the project-based learning (PBL) approach, incorporating YouTube material. Applying the Problem Based Learning (PBL) pedagogy with the digital media platform YouTube, this research seeks to enhance students' numeracy literacy abilities. The participants in this Classroom Action Research (PTK) study are thirty eighth graders from class 8A. There were two rounds to this study. This research measured students' numeracy literacy abilities using data collected via interviews, observations, and tests, which were analysed descriptively. The study found that although students' average exam scores climbed by 14.5 points to 78.2 in Cycle II, they were 63.7 in Cycle I. Results show that eighth graders at SMP Negeri 2 Berbek may benefit from the Problem Based Learning approach, especially in science, when they use YouTube as a learning tool. The researchers recommend doing future experiments over a longer period to examine the persistent influence of YouTube-based PBL on students' numeracy, since the time constraint led to less than optimum results.